'Authentic reproductions': museum collection practices as authentication. (2nd January 2018) - Varutti, Marzia
ABSTRACT: This article investigates the concept of cultural authenticity in museums through an analysis of how indigenous cultural objects in Taiwan are being authenticated by museums as 'indigenous cultural heritage'. In Taiwan, and internationally, indigenous artists and artisans are engaged in the revival of indigenous cultural heritage. Museums are participating in such revival through the acquisition and commission of 'heritage objects', newly made artifacts closely resembling their 'traditional' correspondent (Clifford, James. [2004. "Looking Several Ways: Anthropology and Native Heritage in Alaska." Current Anthropology 45 (1): 5–30.]) I argue that in so doing, museums are authenticating newly made artefacts as indigenous cultural heritage; in the process, a reproduction is turned into an original, and that original into a canon. I propose a theoretical and analytical shift away from the authenticity of the object, and towards authentication that, I suggest, can be understood as a process intrinsic in several museum practices. The ultimate goal of this article is to cast light on the under-researched role of museums as sites for cultural authentication.